Status and determinants of chronic obstructive pulmonary disease awareness, treatment, and control among residents aged 40 years and older in Nanjing city: a cross-sectional study - Huiqing XU; Zhenzhen QIN; Qing YE; Tianrui DENG; Guofeng AO; Fei XU (Zhongguo gonggong weisheng)
ObjectiveTo investigate the awareness, treatment, and control rates of chronic obstructive pulmonary disease (COPD) and their influencing factors among residents aged 40 years and older in Nanjing city to provide a reference for the development of COPD prevention and control strategies in the population. MethodsA total of 2 442 permanent residents aged 40 years and older were recruited from urban communities and rural villages in four districts of Nanjing city, Jiangsu province, using a multistage cluster random sampling method. Face-to-face interviews were conducted using the China Chronic Disease and Nutrition Surveillance Questionnaire, and pulmonary function tests were performed from May 2023 to January 2024. The chi-squared test was used to compare differences in COPD awareness, treatment, and control rates, standardized by the 2020 Jiangsu Provincial Census data, across participant characteristics. Factors influencing these rates were analyzed using multivariable logistic regression models. ResultsOf all participants, 262 (10.73%) were diagnosed with COPD, with a standardized prevalence rate of 11.39%. Of the 262 identified COPD patients, 6.87%, 4.20%, and 3.05% reported awareness, treatment, and control of the disease, with standardized rates of 7.24%, 4.41%, and 2.60%, respectively. Multivariable logistic regression revealed that chronic respiratory symptoms (odds ratio [OR] = 4.91, 95% confidence interval [95%CI]: 1.59 - 15.15), family history of COPD (OR = 18.51, 95%CI: 1.68 - 203.89), and smoking cessation (OR = 9.14, 95%CI: 2.52 - 33.15) were associated with increased odds of COPD awareness. In addition, chronic respiratory symptoms were associated with increased odds of treatment (OR = 11.59, 95%CI: 2.76 - 48.72) and COPD control (OR = 8.66, 95%CI: 1.99 - 37.65). ConclusionsThe prevalence of COPD among residents aged 40 and older in Nanjing is relatively high. However, the awareness, treatment, and control rates of COPD among affected residents remain low. Chronic respiratory symptoms, family history of COPD, and smoking status are the main factors influencing COPD awareness, treatment, and control in this population. Comprehensive measures should be implemented to improve the diagnosis, intervention and management of COPD.